Linking ostracism with employee negligence behavior: a moderated mediation model. Issue 11 (10th September 2022) - Aliza, Komal; Shaheen, Sadia; Malik, Muhammad Jawad; Zulfiqar, Sehar; Batool, Syeda Azra; Ahmad-ur-Rehman, Muhammad; Javed, Ayesha
ABSTRACT: The work-related antecedents of negative behavior are well known, but less is known about cross-domain antecedents, specifically how workplace ostracism affects negligence behavior. Our study aims to address this limitation by considering the Stress-Non-Equilibrium-Compensation (SNEC) Approach and Conservation of Resources (COR) Theory; we propose a moderated mediation model wherein workplace ostracism instigates nurse's negligence behavior through emotional exhaustion, and task interdependence act as the boundary condition. The current study proposed and empirically tested the moderated mediation model. A time-lagged three-wave survey design was utilized and data was collected from (N = 402) nurses. The findings indicate that emotional exhaustion could mediate the relationship between ostracism and nurses' negligence behavior. Furthermore, the results from the moderated mediation analysis suggest that the mediation of emotional exhaustion is moderated by task interdependence such that with a higher level of task interdependence, the mediation effect of emotional exhaustion becomes weaker. Theoretical and managerial implications are discussed.